The impact of organizational behavior on the effectiveness of the organizational role of The Ministry of Health branch in achieving the goals of health transformation in Najran region - Alsharif, Faisal Hussain Faisal; Al Mansour, Ali Mohammed; Al Sulieman, Manassar Zaied Manassar (Journal of Economic, Administrative and Legal Sciences, 2025)
The aim of this study was to examine the impact of organizational behavior on the effectiveness of the organizational role of the Ministry of Health branch in achieving health transformation goals in the Najran region. The researcher employed the descriptive analytical method and distributed a questionnaire to a random sample of (62) employees working at the Ministry of Health branch in Najran. The findings revealed that the level of organizational behavior among employees was high, with an overall mean of (4.14 out of 5). Role performance recorded the highest mean (4.62), followed by helping behavior (4.41), and creative behavior (4.36), while deviant behavior scored the lowest (2.31). Additionally, the mean level of organizational role effectiveness in achieving health transformation goals was very high at (4.39 out of 5). Linear regression analysis confirmed a statistically significant role for the dimensions of organizational behavior (role performance, deviant behavior, helping behavior, and creative behavior) on the effectiveness of the organizational role, explaining 78.1% of the variance in effectiveness, with β coefficients ranging from 0.225 to 0.343, all statistically significant, There are no statistically significant differences in the study sample’s response regarding the impact of organizational behavior on the effectiveness of the organizational role of the Ministry of Health branch in achieving the goals of health transformation in the Najran region according to the variables (gender, age, years of experience). Based on these findings, the researcher recommends providing continuous training opportunities for employees and developing incentive systems to enhance performance and innovation within the framework of health transformation.